Debonding Characteristics of a Polymer Mesh Base Ceramic Bracket Bonded with Two Different Conditioning Methods - Elekdaǧ-Türk, S.; Isci, D.; Ozkalayci, N.; Türk, T. (Oxford University Press, 2009)
The aim of this study was to compare the shear bond strength (SBS) and debonding characteristics of a polymer mesh base ceramic bracket bonded with two different surface conditioning methods. InVu Readi-Base ceramic brackets were bonded to 100 human premolars with different etching protocols. With conventional method (CM), the teeth were etched with 37 per cent phosphoric acid for 30 seconds, while Transbond Plus self-etching primer (SEP) was applied as recommended by the manufacturer. SBS testing was performed on 25 samples of each group while the remaining 25 samples of each group were subjected to plier or machine debonding after thermocycling for 1000 cycles. The adhesive remnant index (ARI) was used to determine the amount of composite resin on the enamel. Statistical analysis included Kruskal-Wallis and Mann-Whitney U-tests and Weibull analysis.No significant difference was observed between the CM (9.22 MPa) and SEP (9.04 MPa) groups (P = 0.684). ARI scores of machine and plier debonding for both groups showed a significant difference (P ≤ 0.0001). Debonding with pliers showed a pronounced number of ARI scores of 3 for both groups. Polymer mesh base fractures were observed for both groups. Nevertheless, no significant differences were observed between the groups (χ2 = 4.304, P = 0.230).The results of this in vitro study are encouraging, since, for the majority of specimens, all of the residual adhesive remained on the enamel surface. This type of debonding pattern has the advantage of protecting the enamel surface. Nevertheless, the base fractures at the ceramic/polymer interface might necessitate modifications in debonding strategy.